(untitled) (European Journal of Pure and Applied Mathematics, 2024)
This paper aims to introduce and study two new operators (.)^_ω and cl^_ω(·) by utilizing the notion of primal defined by S. Acharjee et al. Also, we investigate some fundamental properties of them. In addition, we showed that the operator cl^_ω(.) satisfied the Kuratowski closure axioms. Therefore, we obtain a new topology denoted by τ^_ω, which is finer than the original one. Moreover, the topology τ^_ω obtained via the operator cl^_ω(·) is finer than τ_ω, where τ_ω is the family of all ω-open subsets of a primal topological space (X,τ,P). Furthermore, we not only examine the fundamental properties of this class of sets but also provide some counterexamples.